2012
DOI: 10.1021/ol300434m
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Azaspirocycles via Iron Trichloride-Promoted Cyclization/Chlorination of Cyclic 8-Aryl-5-aza-5-tosyl-2-en-7-yn-1-ols

Abstract: A simple and efficient FeCl(3)-promoted cyclization/chlorination of cyclic tosylamine-tethered 8-aryl-2-en-7-yn-1-ols was observed. The reaction proceeded instantaneously at 23 °C in air to afford (Z)-4-(arylchloromethylene)-substituted azaspirocycles in good to excellent yields. This transformation can also be applied to the synthesis of spirocarbocyclic analogues from cyclic 8-aryl-2-en-7-yn-1-ols and FeCl(3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…[18] The (Z)-4-(arylchloromethylene)-substituted azaspiro [4.6] The research group of Yeh in 2012, reported an intramolecular spirocyclization-chlorination of alkyne-tethered cyclic alcohols under FeCl 3 catalysis (Scheme 16A). [19] This synthetic route provides the access to (Z)-4-(arylchloromethylene)-substituted azaspirocycles 44 and spirocarbocyclic analogues 45 from 46 and 47 respectively, in good to excellent yields. The reaction rates are very high (1 min reaction time) and proceeds even in the presence of air.…”
Section: Cyclizative Coupling Strategiesmentioning
confidence: 96%
“…[18] The (Z)-4-(arylchloromethylene)-substituted azaspiro [4.6] The research group of Yeh in 2012, reported an intramolecular spirocyclization-chlorination of alkyne-tethered cyclic alcohols under FeCl 3 catalysis (Scheme 16A). [19] This synthetic route provides the access to (Z)-4-(arylchloromethylene)-substituted azaspirocycles 44 and spirocarbocyclic analogues 45 from 46 and 47 respectively, in good to excellent yields. The reaction rates are very high (1 min reaction time) and proceeds even in the presence of air.…”
Section: Cyclizative Coupling Strategiesmentioning
confidence: 96%
“…Anhydrous iron(III) chloride and its hexa-hydrate feature widely in contemporary organic syntheses, since, because of their Lewis acid properties, they can initiate or catalyze a variety of organic transformations [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Because of their redox properties arising from the 1e − , Fe III /Fe II redox transformation, they are also the basis of a useful polymerization process [ 27 , 28 , 29 , 30 , 31 ], for example the polymerization of thiophene.…”
Section: Iron(iii) and Copper(ii) Chlorides As Chlorination Catalymentioning
confidence: 99%
“…Another method involved a zinc halides‐catalyzed cycloaddition of propargyl halides with cyclopentadiene, producing the 5‐[aryl(halo)methylene]bicyclo[2.2.1]hept‐2‐enes in low yields 8. Based upon our previous experience with Lewis acid‐promoted carbohalogenations of C‐2 and C‐3 propargyl‐tethered cyclic 2‐enols providing fused9a and spiro bicycles,9b respectively, we anticipated that cyclic 2‐enols bearing a 3‐arylpropargyl tether at the C‐4 position of the ring may alter the reaction path and lead to bridged bicyclic skeletons bearing an exo ‐methylene group. Herein, we describe a Lewis acid‐promoted carbohalogenation of cyclic C‐4‐(3‐aryl‐prop‐2‐ynyl)‐tethered 2‐enols to generate bridged bicyclic compounds having an ( E )‐aryl(halo)methylene group at the C‐5 position.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%